Pencegahan Stunting melalui Pelatihan Pemberian ASI Eksklusif dan Makanan Pendamping ASI (MP ASI) - Khoiriyah Isni; Siti Muthia Dinni (Jurnal Pengabdian Pada Masyarakat, 2020)
PREVENTION OF STUNTING THROUGH EXCLUSIVE BREASTFEEDING TRAINING AND ASI COMPLEMENTARY FOOD (MP ASI). Randugunting Hamlet is one of the hamlets that have the highest number of children under five in the area of Tamanmartani Village, Kalasan, Sleman, DIY. Meanwhile, parenting patterns that are less responsive and supportive in breastfeeding and breastfeeding are suspected to be factors that trigger nutritional health problems of children under five. It is due to the ignorance of parents and caregivers in providing exclusive breastfeeding and complementary feeding according to WHO standards. This situation is very high-risk accounts for the number of stunting cases in Indonesia. Especially in Sleman Regency, so that the Community Partnership Program Proposal Team conducts community empowerment activities. It is the form of training in the context of stunting prevention. The targets of this activity are pregnant women, mothers who have toddlers, and health cadres. The method of activities used includes the provision of health education, simulations, and training or practice through the MP ASI cooking competition and process evaluation. Increased knowledge and target skills in exclusive breastfeeding and MP ASI standard WHO is the output of this empowerment activity. Besides, the dissemination of events in the form of scientific publication products and training modules. In general, this empowerment activity can increase target knowledge and skills. The evaluation of the process shows the enthusiasm of the target in implementing the knowledge that the Proponent Team provided through health education and simulations. It hoped that this activity could be continue in other hamlets located in the Tamanmartani village area. It can contribute to preventing and reducing the number of stunting cases in Indonesia.